Pengaruh Digital Marketing dan Customer Relationship Management Terhadap Keputusan Pemebelian pada Gedung Serbaguna Graha Farimah Gultom (GFG) Medan - Adawiyah, Rohimah; Amelia, Wan Rizca (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This research aims not only to determine the influence of Digital marketing and Customer Relationship Management on purchasing decisions for renting the Graha Fatimah Gultom (GFG) Multipurpose Building in Medan, but as a solution to increase building usage after experiencing a decline due to Covid 19 and thereafter there has been no increase.    The type of research used in this research is associative research to see the relationship between the variables studied. With 441 total tenants recorded in 2017-2022 forming the population, the research sample in this study consisted of 70 tenants obtained using the Slovin formula. The data collection technique uses a questionnaire distributed to the sample. The data analysis technique used is multiple regression analysis. The research results show that digital marketing has a significant effect on purchasing decisions (tcount 5.116 ttable 1.667) with a significance value of 0.000 0.05, Customer Relationship Management has a significant effect on purchasing decisions (tcount 4.387 ttable 1.667) with a significance value of 0.000 0.05. Furthermore, together digital marketing and Customer Relationship Management have a significant effect on purchasing decisions (F count 32,617 F table 3.10) with a significance value of 0.000 0.05.